Attitude and practices of health workers towards the documentation of medical records at Mulago National Referral Hospital. A cross-sectional study. - Nalugya Angella, Robinah; Orishaba, Glorious (SJ Insights, 2025)
Background Documentation is essential for ensuring safe, high-quality, and continuous patient care and research work. The study aimed to identify the attitudes and practices of health workers towards the documentation of medical records at Mulago National Referral Hospital. Methodology A cross-sectional study design. A sample size of 35 health workers was used, and a purposive sampling technique was used in the study. Results The majority 20(57.14%) of respondents were above 40 years, and least 15(42.86%) were between 25-40 years of age. 33(94.29%) communication was more essential during the documentation of medical records, followed by continuous patient care, 30(85.71%). 10(28.57%) considered accuracy as one of the principles followed when documenting medical records, 8(22.86%) timeliness, and the least 4(11.43%) completeness. 30(85.71%) considered documentation a burden. 31(88.57) used paper-based/manual systems for documentation, while the least 4(11.43%) used electronic systems. 25(71.43%) are not trained about the required documentation knowledge, while the least 10(28.57%) are trained. 34(97.14%) documents manually and 1(2.86%) document electronically. 25(71.14%) are familiar with the required documentation knowledge while the least 10(28.57%) are not. The majority, 27(77.14%), document anytime a case is rendered while the least 8(22.86%) don’t. Conclusion Health workers had a poor attitude towards the documentation of medical records, and poor practices during the documentation of medical records. Recommendation The hospital administrators to design appropriate penalties for all health workers who carry out poor documentation practices of patient medical records. These may include: a deduction of payment for the given time.